Perspectives on Drought Preconditioning Treatments With a Case Study Using Western Larch - Moler, Ehren Reid Von; Nelson, Andrew Steven (Frontiers in Plant Science, 2021)
As the demand for drought hardy tree seedlings rises alongside global temperatures, there is a need to optimize nursery drought preconditioning methods to improve field performance of planted seedlings. This perspective article advocates for a more holistic approach to drought preconditioning research that considers the moderating role of plant developmental stage on the effects of drought preconditioning. We identify discrepancies in past studies of root growth potential responses to drought preconditioning and highlight studies that suggest such discrepancies may result from inconsistencies among studies in the timing of drought preconditioning implementation. We then illustrate our perspective by presenting original research from an aeroponic root growth potential trial of first-year western larch (Larix occidentalis Nutt.) seedlings exposed to three soil moisture contents for six months. We evaluated whether drought preconditioning could be used to increase the ratio of root : foliar tissue mass or enhance seedling physiological vigor during a subsequent growth period. Drought preconditioning was found to increase the ratio of root : foliar tissue mass and enhance seedling physiological vigor. Specifically, soil moisture content related negatively with new root biomass, positively with new foliar biomass, and negatively with the length and number of new roots (P < 0.001). Meanwhile, the mass of lateral root production following drought preconditioning, but prior to aeroponic growth, correlated weakly to the mass, count, and length of new roots produced during aeroponic growth. We propose that evaluating the importance of the timing of drought preconditioning treatments constitutes an important research frontier in plant science.